TECHNOSTRESS: TRENDS AND CHALLENGES IN THE 21ST CENTURY KNOWLEDGE MANAGEMENT - Laspinas, Marilyn L. (European Scientific Journal, ESJ, 2015)
Technostress is the trends and challenges of the librarians in the 21st century knowledge management. It is a modern disease of adaptation caused by an inability to cope with the new technologies in a healthy manner. It manifests itself in the struggle to accept technological innovations. The study sought to answer the following: what is the profile of the librarians; what is the level of technostress of librarians in terms of physical, emotional, behavioral, and psychological; and how did the librarians cope with technostress? The study employed descriptive survey method. This method seeks to ascertain respondents’ perspectives on technology stress related in a predetermined structured manner. With the total of twenty nine (29) professional librarians who enrolled the MLIS program for second semester 2013-2014. Results showed that librarian is a female dominated profession. On the other hand, librarians are slightly affected physically by stress coming from the technology. Moreover, the coping strategies of librarians for physical aspects, despite the fact that librarians sometimes experienced to do exercise, do some deep breathing, and follow proper diet. However, the emotional aspects, the librarians often listen to music, and sometimes stay calm, maintain a sense of humor, talk with others or find a mentor to confide with, and meditate. In like manner, when it comes to behavioral aspects the librarians sometimes utilizes effective time management, establishes a teamwork relationship, and take a technology time-out and seldom do some job rotation. Thus, the psychological aspects, the librarians oftentimes realized that the only thing constant is change, and go with the flow. Every technological change or problem librarians have to deal with is an opportunity to learn something and balance positive and negative thoughts. Furthermore, stress influences human behavior whether in illness or in health and it is the body’s nonspecific response to a demand placed on it.